Irritable bowel syndrome and inflammatory bowel disease overlap syndrome: pieces of the puzzle are falling into place - Rafiz Abdul Rani; Raja Affendi Raja Ali; Yeong Yeh Lee (Intestinal Research, 2016)
Irritable bowel syndrome (IBS), a common gastrointestinal disorder involving the gut-brain axis, and inflammatory bowel disease (IBD), a chronic relapsing inflammatory disorder, are both increasing in incidence and prevalence in Asia. Both have significant overlap in terms of symptoms, pathophysiology, and treatment, suggesting the possibility of IBS and IBD being a single disease entity albeit at opposite ends of the spectrum. We examined the similarities and differences in IBS and IBD, and offer new thoughts and approaches to the disease paradigm.